Through the eyes of a whistle-blower : how Sherry Hunt spoke up about Citibank's mortgage fraud - Waytz, Adam, (SAGE knowledge. Cases., 2016)
In 2011, Sherry Hunt was a vice president and chief underwriter at CitiMortgage headquarters in the United States. For years she had been witnessing fraud, as the company bought billions of dollars in mortgage loans from external lenders that did not meet Citi credit policy and sold them to government-sponsored enterprises (GSEs). This resulted in Citi selling to GSEs such as Fannie Mae and Freddie Mac pools of loans that were considerably defective and thus likely to default. This study explains how - and why - Sherry Hunt exposed Citibank's fraudulent activities.